SWOT analysis of manufacturing company. Food industry case "KRÓL Bakery" - Król Tatiana (My University, 2008)
The goal of this paper is to identify and describe external and internal environment of Bakery Król. Moreover it defines strategy and sample strategic moves that the company should make. The first chapter - “Organization of business activity – theoretical issues” - is a theoretical outline of entrepreneurship essence. It helps to allocate Bakery Król on the market. The second chapter - “SWOT Analysis of a company”- describes different types of business strategies and its methods that the company may use. Furthermore, it presents the details of SWOT analysis. In the third chapter - “SWOT Analysis of Bakery KRÓL Antoni in Katowice”- we can find description of a company and its environment – SWOT analysis. In addition, some sample strategic moves that the company may use in order to keep its position on the market – TOWS analysis. All information that is needed to run such analysis was gathered through interviews with owners, and internal documents of the company.
Analiza SWOT przedsiębiorstwa produkcyjnego. Studium branży spożywczej na przykładzie Piekarni "KRÓL"
Keywords: entrepreneurship; medium-sized business; business strategy formulation; strategic analysis; SWOT analysis